Students’ Learning Outcomes and Activities: The Use of Video Conference during COVID-19 Pandemic - Arieny, Mutiara; Tibrani, Mgs. Muhammad; Santri, Didi Jaya (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2021)
This research was motivated by problems during the covid-19 pandemic, it showed that the students’ activity and learning outcomes of the topic of Ecosystem at Public High School 10 Palembang remain low. Based on observations of the electronic learning process carried out at the school, the teacher mostly applies asynchronous learning, thus the interactivity between teacher and students is not performed well. This study aimed to find out the effect of using video conferencing on the topic of Ecosystem toward the activities and learning outcomes of students. This study was set up as a quasi-experiment, using a nonequivalent control group design with two groups. The experimental group (Grade 10 of MIA 2) which do e-learning using video conference and the control group (Grade 10 of MIA 4) where e-learning without using video conference. Both groups were selected randomly. Data collection instruments were learning activity observation sheets and biology learning outcomes tests. Learning activity was analyzed quantitatively, while the learning outcomes data were also run quantitatively on a prerequisite test, hypothesis testing and the N-gain test. The results show the average percentage of experimental class learning activities increased from 39.5% to 42.5% while the control class did not increase. The Ancova test showed a significance value of 0.000 or less than = 0.05 and the N-gain test was 0.36. Based on the results, the use of video conferencing on the topic of Ecosystem significantly affected the learning outcomes improvement.